WEBSITE SPECIFICATIONS HONDA VARIO USING MACROMEDIA DREAMWEAVER MX. - Romli jabar; Cut Asiana Germawaty, SKom, MMSI (Jurnal Sistem Informasi, 2007)
Rapid technological advances encourage people to get information quickly and up to date (the latest), especially facilities that began ogled as a media campaign that was quite interesting. This method is considered successful in meeting information needs. For that the author wants to provide information about the specifications of the Honda motorcycle Vario to consumers who want to buy a motorcycle that appears matic is elegant and stylish. The site is expected to make it easier for consumers to look for references motorcycles in buying.